Wakes of four complex bodies of revolution at zero angle of attack - Atli, Veysel (American Institute of Aeronautics and Astronautics (AIAA), 1989)
The wakes of four complex bodies of revolution were investigated experimentally with a constant-temperature hot-wire anemometer. All tests were performed at a low Mach number (Moo — 0.1) and zero angle of attack. Mean and turbulence velocity profiles were obtained along and across the wakes. The structure of the axisymmetric wake and the effects of the geometric differences of the models on their wakes were investigated.